Genetic basis for the cooperative bioactivation of plant lignans by Eggerthella lenta and other human gut bacteria - Bess, Elizabeth N.; Bisanz, Jordan E.; Yarza, Fauna; Bustion, Annamarie; Rich, Barry E.; Li, Xingnan; Kitamura, Seiya; Waligurski, Emily; Ang, Qi Yan; Alba, Diana L.; Spanogiannopoulos, Peter; Nayfach, Stephen; et al. (Nature microbiology, 2020)
Plant-derived lignans, consumed daily by most individuals, are thought to protect against cancer and other diseases 1 ; however, their bioactivity requires gut bacterial conversion to enterolignans 2 . Here, we dissect a four-species bacterial consortium sufficient for all five reactions in this pathway. A single enzyme (benzyl ether reductase, encoded by the gene ber ) was sufficient for the first two biotransformations, variable between strains of Eggerthella lenta , critical for enterolignan production in gnotobiotic mice and unique to Coriobacteriia. Transcriptional profiling (RNA sequencing) independently identified ber and genomic loci upregulated by each of the remaining substrates. Despite their low abundance in gut microbiomes and restricted phylogenetic range, all of the identified genes were detectable in the distal gut microbiomes of most individuals living in northern California. Together, these results emphasize the importance of considering strain-level variations and bacterial co-occurrence to gain a mechanistic understanding of the bioactivation of plant secondary metabolites by the human gut microbiome. A consortium of four human gut microbiota species, including Eggerthella lenta , can convert plant-derived lignans into bioactive enterolignans via a five-step pathway, providing mechanistic insight into the production of these protective metabolites.